Estrategias motivacionales y su incidencia en la calidad de atención que brindan el personal administrativo de la Dirección Distrital de Educación 12D01 Baba-Babahoyo-Montalvo - Villegas Lamilla, Jenniffer Licenia (2019)
This research work entitled Motivational Strategies and their impact on the quality of care provided by the administrative administrative staff of the District Directorate of Education 12D01 Baba-Babahoyo-Montalvo, is carried out with the objective of knowing the motivational strategies that employ the departmental heads with their subordinates and these as they use it during the process of attention to the users and in this way to determine the quality of attention provided by the administrative staff. For this, they have taken different motivational theories that express a clear explanation of this process, which is the basis of the study, and reaffirms the level of motivation of employees. This research is developed under a non-experimental design, and based on a causal correlational study, which determines the relationship between the motivational strategies and the quality of care provided by the administrative staff of the 12D01 district address. Motivation is fundamental within the care process, quality and even user satisfaction depends on it, a fully motivated staff allows the growth and strengthening of any company, be it public or private, even more institutions dedicated to the educational service. The administrative employees when they have a very good motivation their work performance will be of quality, not necessarily speaking of an economic motivation but of the most important one in the human beings, the emotional motivation. Precisely, her motivational state allows her to channel effort, energy and unwind in a pleasant working environment, where she performs her work with the greatest tranquility and love.